Attitudes and experiences of nursing staff to the Mental Health Act 2001: lessons for future mental health legislation. (10th March 2014) - Doherty, A. M.; Jabbar, F.; Kelly, B. D.
Abstract : Objectives: The Mental Health Act 2001 was implemented in 2006 to bring Ireland into line with international practice and United Nations Conventions on Human Rights. Previous studies have reported some practical difficulties for the professionals involved. We wished to examine the experiences of nursing staff and the impact of the Act on clinical nursing practice since its implementation. Method: This cross-sectional survey was conducted by questionnaire. It contained questions examining training in and attitudes to the Act, and any resultant changes in nursing practise. Results: A total of 317 questionnaires were returned. Of the nurses, 92% reported having received training in the Act, and 56% of nursing staff believed that their workload had increased as a result of the change in legislation. Of those who made a comment, 76.5% were negative, with increased paper work, lack of clarity and an excessive focus on legalities being the most common difficulties reported. Conclusions: Nursing staff have shown mixed attitudes to the Mental Health Act 2001, but many of the difficulties encountered are similar to those experienced by other professionals.